Two Centers for the Gifted, One Moon - The Program - Bengio, Efrat; Margaliot, Adva; Saar-Hyams, Ronit; Benakovic, Ksenija (International Journal for Talent Development and Creativity, 2021)
This article addresses a unique program involving international collaboration between gifted students from Israel and Croatia. The COVID-19 pandemic opened an opportunity for effective synchronous communication that enabled an unmediated connection between the participants. During the program the children researched the moon from various aspects: scientific, emotional-behavioral and artistic, via theater and creative writing. There were 35 gifted students, 20 from Israel and 15 from Croatia. Five teachers of gifted students, an educational counselor, an educational psychologist and the writers of this article participated in the program and provided the students with academic accompaniment in giftedness and creativity.